The Determinants of Gold Price for top 5 countries producer of gold in the world / Nurul Anis Afiqa Azaman - Azaman, Nurul Anis Afiqa (2017)
The main purpose of this paper is to analyse the determinants of gold price in top 5 countries producer of gold in the world. Gold is the metals that have high value for a people and considered as a precious one. The gold market is broad and complex, so to understanding the exact statistical of supplier and demander is very crucial. Gold is being studied due to its volatility price that is determined by several financial factors. A total of 5 countries is being selected which is China, Australia, Russia, United States and Canada. This is being selected due to their position as top producer of gold in the world. The gold price is based on individual currency of the country. While, the variables that used in this study are interest rate in percentage, exchange rate in percentage, real interest rate in percentage, gross domestic product annual growth in percentage and money supply M2 annual changes in percentage. This study will observed the data for total of 21 years that started from year 1995 until 2016 in annually basis.